Carbon encapsulated heterojunction composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202610902211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-06-23
AI Technical Summary
本发明的目的旨在通过盐模板辅助冷冻干燥结合一步高温固相反应,解决现有技术中异质结构筑与碳封装难以同步、组分分散性差、工艺复杂等问题
一步原位合成:无需多步反应,避免中间产物转移造成的损失和污染,适合放大生产。
Smart Images

Figure CN122426716B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage and nanomaterial synthesis, specifically relating to a method for preparing carbon-encapsulated molybdenum diselenide / tungsten diselenide heterojunction composite material using a salt template-assisted freeze-drying-one-step high-temperature solid-state reaction method, and the application of this material in potassium-ion battery anodes and potassium-ion hybrid capacitors. Background Technology
[0002] Transition metal selenides are considered promising anode materials for potassium-ion batteries due to their high theoretical capacity and rich redox chemistry. However, their inherent low conductivity, severe volume expansion, and the dissolution of polyselenides during charge and discharge severely limit their cycle stability and rate performance. Constructing heterojunctions and combining them with carbon materials are effective strategies to solve these problems.
[0003] Common methods for preparing transition metal selenide / carbon composites in the prior art include: Hydrothermal / solvothermal methods: Although nanostructures can be obtained, they usually require subsequent high-temperature selenization treatment, which is complicated and the resulting carbon layer and selenide are mostly physically mixed with weak interfacial bonding; at the same time, it is difficult to introduce two metal elements to form atomic-level heterojunctions.
[0004] Chemical vapor deposition (CVD) is costly and has low yield, making it unsuitable for large-scale production.
[0005] Hard stencil method: Stencil removal requires etching with strong acid or strong alkali, which damages the material structure and makes it difficult to control the thickness of the carbon layer.
[0006] The main drawbacks of existing technologies for MoSe2 / WSe2 heterojunction composites include: There is a lack of a simple method that can simultaneously achieve in-situ construction of heterostructures, uniform encapsulation of carbon layers, and high dispersion of components.
[0007] Existing methods often result in severe separation of the MoSe2 and WSe2 phases, a low proportion of heterogeneous interfaces, and an insignificant synergistic effect.
[0008] Uneven mixing of carbon source and inorganic precursor leads to excessively thick carbon layer or localized exposure, which cannot effectively suppress volume expansion and selenium dissolution.
[0009] The aforementioned defects are difficult to resolve within the industry, primarily due to the following difficulties: Challenge 1: Integrated synthesis of heterojunctions and carbon encapsulation. Traditional two-step methods (first preparing the heterojunction, then encapsulating it with carbon) are prone to causing damage to the heterojunction interface during carbon encapsulation or phase separation at high temperatures. There is an urgent need in this field for an in-situ one-step method that allows the carbonization and selenization reactions to proceed synergistically in space.
[0010] Challenge 2: Precursor dispersion uniformity. Direct mixing of molybdenum, tungsten, selenium, and carbon sources easily leads to agglomeration, resulting in uneven component distribution in the product. A microscale confinement method is needed to pre-"freeze" each component into a uniformly mixed state.
[0011] Challenge 3: Precise control of carbon layer thickness and pore structure. A carbon layer that is too thick will hinder ion transport, while one that is too thin will have insufficient buffering effect. Conventional methods struggle to achieve both.
[0012] Therefore, developing a simple, efficient, and controllable integrated synthesis strategy to achieve the controllable preparation of carbon-encapsulated MoSe2 / WSe2 heterojunction composites is of great research significance and application value. Summary of the Invention
[0013] To address the shortcomings of existing technologies, this invention employs a soluble inorganic salt (e.g., KCl) as a salt template. Molybdenum, tungsten, selenium, and carbon sources are dissolved, and then freeze-dried to uniformly solidify the components on the surface and in the interstices of the salt crystals, forming a "salt-precursor" composite. Subsequently, high-temperature calcination is performed under an inert atmosphere, during which three key processes occur simultaneously: pyrolysis and carbonization of the carbon source, forming an amorphous carbon matrix; decomposition of ammonium molybdate / ammonium tungstate into MoO3 / WO3, which is then reduced and selenized by Se vapor generated from the decomposition of selenite, generating MoSe2 and WSe2 nanosheets in situ; due to the spatial confinement effect of the salt template, MoSe2 and WSe2 are in close contact within the carbon layer, forming a heterogeneous interface. Finally, the salt template agent is removed by washing with water, yielding a pure carbon-encapsulated MoSe2 / WSe2 heterojunction composite material. The purpose of this invention is to solve the problems of difficulty in simultaneously constructing heterogeneous structures and carbon encapsulation, poor component dispersion, and complex processes in existing technologies by combining salt template-assisted freeze-drying with a one-step high-temperature solid-state reaction. Meanwhile, the resulting material possesses both high rate performance and ultra-long cycle stability, making it suitable for potassium-ion batteries and potassium-ion hybrid capacitors.
[0014] The technical solution adopted in this invention is as follows: In a first aspect, the present invention provides a method for preparing a carbon-encapsulated heterojunction composite material, comprising the following steps: (a) Dissolve molybdenum source, tungsten source, selenium source, carbon source and salt template agent in a solvent to form a precursor solution; (b) Freeze-dry the precursor solution to obtain a solid precursor; (c) Under an inert atmosphere, the solid precursor is heated to 650-800°C for calcination to obtain the calcined product; (d) Wash and dry the calcined product to remove the salt template agent, and obtain carbon-encapsulated molybdenum diselenide / tungsten diselenide heterojunction composite material.
[0015] In step (a), the molybdenum source is ammonium molybdate, the tungsten source is ammonium tungstate, and the selenium source is selenite; the carbon source is carrageenan, sodium alginate, chitosan, starch, glucose, or sucrose, preferably carrageenan. Carrageenan not only serves as a carbon source, but the reducing gases (H2, CO, etc.) released during its pyrolysis can also assist in the reduction of Mo by Se vapor. 6+ / W 6+ This promotes the complete selenization reaction and simultaneously forms a conductive network through carbonization, achieving a synergistic match between the carbon source and the selenium source; the salt template agent is potassium chloride, sodium chloride, or lithium chloride; preferably potassium chloride.
[0016] In step (a), the molar ratio of the molybdenum source to the tungsten source is 1:0.5~2, and the amount of the selenium source is 2~4 times the total molar amount of the molybdenum source and the tungsten source; the mass of the salt template agent is 10-20 times the total mass of the molybdenum source, the tungsten source, the selenium source and the carbon source, to ensure the formation of a continuous salt template network and to achieve microscopic confinement of the precursor.
[0017] In step (a), the solvent is deionized water.
[0018] In step (b), after the ice crystals sublimate, a porous framework is left behind, and the precursor components are uniformly attached to the surface of the salt template agent (e.g., KCl) crystals to avoid macroscopic agglomeration during subsequent calcination.
[0019] In step (b), the freeze-drying temperature is -50°C to -30°C, and the time is 24-48 hours. This invention employs freeze-drying pretreatment to pre-freeze each component in a uniformly mixed state, avoiding component migration and agglomeration caused by ordinary drying.
[0020] In step (c), the heating rate of the calcination is 1-5℃ / min, and the holding time is 0.5-3 hours.
[0021] Reaction mechanism: 200-300℃: Carrageenan decomposes, generating a carbon skeleton and releasing reducing gases (H2, CO, etc.). 400-500℃: Selenite decomposes into SeO2, which is then reduced to Se vapor; 500-700℃: MoO3 / WO3 is selenized by Se vapor to form MoSe2 and WSe2, while carbon layers are coated in situ.
[0022] The heating rate in this step needs to be controlled (1-5℃ / min). Too fast a rate can easily cause the carbon layer to crack. The holding temperature needs to be between 650-800℃. Too low a temperature will result in poor crystallinity, while too high a temperature will lead to excessive growth of heterojunctions.
[0023] In step (d), wash with deionized water 3-6 times until no white precipitate is produced when AgNO3 solution is added to the washing solution, indicating that chloride ions have been completely removed.
[0024] Secondly, a carbon-encapsulated heterojunction composite material prepared by the method is provided.
[0025] Its structural features are as follows: The morphology of the composite material was characterized by scanning electron microscopy (SEM). The results showed that the composite material exhibited a macroscopic layered morphology, with MoSe2 / WSe2 nanosheets tightly anchored on the ultrathin carbon matrix. The carbon matrix was semi-transparent, confirming the formation of a thin-layer carbon coating structure.
[0026] Transmission electron microscopy (TEM) and high-resolution TEM results showed that the nanosheets were uniformly dispersed in the carbon matrix, with no obvious stacking observed. The carbon layer was an amorphous structure (light gray, without lattice fringes), tightly wrapped around the edges of the selenide nanosheets, forming a "carbon encapsulation" structure. Clear lattice fringes were observed inside the nanosheets, indicating their high crystallinity. Furthermore, a continuous and ordered atomic arrangement existed within the nanosheets, exhibiting a quasi-Mohr superlattice structure, confirming the successful construction of the MoSe2 / WSe2 heterostructure. The clear boundary between the amorphous carbon and the crystalline selenide indicated strong interfacial interactions, which are beneficial for electron transport and lay the structural foundation for enhanced electrochemical performance.
[0027] Furthermore, the thickness of the ultrathin carbon layer is 2-5 nm.
[0028] Thirdly, the present invention provides the application of the carbon-encapsulated heterojunction composite material in the preparation of potassium-ion battery anodes or potassium-ion hybrid capacitor anodes.
[0029] Fourthly, the present invention provides a potassium-ion battery, wherein the negative electrode comprises the aforementioned carbon-encapsulated heterojunction composite material.
[0030] Fifthly, the present invention provides a potassium-ion hybrid capacitor, wherein the negative electrode comprises the aforementioned carbon-encapsulated heterojunction composite material.
[0031] Compared with the prior art, the present invention has the following beneficial effects: 1. Advantages of the method itself One-step in-situ synthesis: No multi-step reaction is required, avoiding losses and pollution caused by the transfer of intermediate products, making it suitable for large-scale production.
[0032] Raw materials are inexpensive and readily available: Ammonium molybdate, ammonium tungstate, selenite, carrageenan, and KCl are all common chemicals, resulting in low overall costs.
[0033] Mild conditions: No autoclave required, only a regular tubular furnace; the elution template uses only water, requiring no strong acids or alkalis, making it mild and environmentally friendly, and does not damage the product structure.
[0034] Adjustable product structure: By changing the amount of carbon source, calcination temperature, and salt template ratio, it is possible to control the carbon layer thickness, heterojunction size, and specific surface area to meet the needs of different application scenarios.
[0035] Good batch repeatability: Freeze-drying ensures the uniformity of the precursor, and it is expected that the phase structure and electrochemical performance of multiple batches of products can maintain a high degree of consistency.
[0036] 2. Material performance advantages The carbon-encapsulated MoSe2 / WSe2 heterojunction composite material prepared in this invention exhibits significantly better electrochemical performance than single-component materials in potassium-ion batteries: after 2000 cycles at 5 A / g, the capacity remains at 190 mAh / g (87.9% retention). + It exhibits a high diffusion coefficient and stable electrodes after cycling. A potassium-ion hybrid capacitor assembled using this MoSe2 / WSe2 / C material achieves an energy density of 155 Wh / kg at 0.5 A / g, and retains 95.6% capacity after 10,000 cycles at 10 A / g, demonstrating superior overall performance compared to previously reported similar materials.
[0037] 3. Comparison with existing methods Compared with the commonly used hydrothermal / solventothermal carbon coating method, chemical vapor deposition method or hard template method in the prior art, the salt template-assisted freeze drying-one-step high temperature solid-state reaction method proposed in this invention (which completes five key steps of carbonization, reduction, selenization, heterojunction formation and carbon encapsulation in the same heat treatment process) has significant advantages.
[0038] Firstly, at the process level, traditional hydrothermal methods typically require the preparation of selenides before carbon encapsulation, which is cumbersome and results in only physical contact between the carbon layer and the selenides, leading to weak interfacial bonding. In contrast, this invention achieves in-situ construction of the MoSe2 / WSe2 heterojunction and conformal encapsulation of the ultrathin carbon layer simultaneously by freeze-drying the molybdenum source, tungsten source, selenium source, and carbon source in a KCl salt template followed by one-step calcination. This significantly simplifies the process and eliminates the need for expensive equipment or strong acid / alkali etching of the template.
[0039] Secondly, at the product structure level, the composite material obtained by this invention forms an atomically matched quasi-Mohr superlattice heterostructure interface between MoSe2 and WSe2, and the carbon layer thickness is uniform (2-5 nm), which is far superior to the physical mixture product obtained by traditional methods.
[0040] More importantly, in terms of electrochemical performance, the anode material prepared by the method of this invention achieved a capacity retention of 190 mAh / g (87.9%) after 2000 cycles at 5 A / g in a potassium-ion battery, while previously reported MoSe2 or WSe2-based anodes typically showed significant capacity degradation after no more than 500 cycles under the same test conditions. These performance advantages are directly attributed to the unique "carbon encapsulation-heterojunction integration" structure of the method of this invention, which is achieved through the confinement effect of the salt template and the uniform mixing through freeze-drying, making it difficult to replicate by existing methods.
[0041] In summary, the method of this invention is simple, scalable, and requires no expensive equipment. It overcomes the technical bias of existing technologies that make it difficult to synergistically construct heterojunctions and carbon layers, and provides a new scalable preparation route for high-performance selenide-based anode materials.
[0042] 4. Unexpected technical effects (1) Spontaneous formation of quasi-Mohr superlattice: According to conventional understanding, MoSe2 and WSe2, two selenides with similar but different lattice constants, tend to separate or form disordered solid solutions in high-temperature solid-state reactions. However, this invention unexpectedly promotes the spontaneous formation of an atomically matched quasi-Mohr superlattice heterostructure through the synergistic effect of salt template confinement and carbon encapsulation. This long-range ordered superstructure can be obtained without epitaxial growth, which is completely beyond the expectations of those skilled in the art.
[0043] (2) Strong synergistic effect: The electrochemical performance of the MoSe2 / WSe2 / C composite material far exceeds the expected linear superposition. Its rate performance (182 mAh / g at 10 A / g) and cycle life (87.9% retention after 2000 cycles) are not only significantly higher than those of the single component, but also more than twice the sum of their performance. This strong synergistic effect is something that those skilled in the art cannot directly predict from the performance of the single component. Attached Figure Description
[0044] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0045] Figure 1 The X-ray diffraction (XRD) spectra of the MoSe2 / C, WSe2 / C, and MoSe2 / WSe2 / C composite materials prepared in Examples 1-3 are shown.
[0046] Figure 2 The images shown are scanning electron microscope (SEM) images of the MoSe2 / WSe2 / C composite material prepared in Example 3; where A is a high-magnification SEM image (scale bar 2 μm) and B is a high-magnification SEM image (scale bar 200 nm).
[0047] Figure 3 The images shown are transmission electron microscope (TEM) images of the MoSe2 / WSe2 / C composite material prepared in Example 3; where A is a low-magnification TEM image (scale bar 5 nm) and B is a high-magnification TEM image (scale bar 2 nm).
[0048] Figure 4 The rate performance diagrams are obtained by using the MoSe2 / C, WSe2 / C and MoSe2 / WSe2 / C composite materials prepared in Examples 1-3 of this invention as negative electrodes of potassium-ion batteries.
[0049] Figure 5 The energy-power density curve (Ragone plot) was obtained by using the MoSe2 / WSe2 / C composite material prepared in Example 3 of the present invention as the electrode of a potassium ion mixed capacitor.
[0050] Figure 6 The cycle life diagram of the potassium ion hybrid capacitor assembled from the MoSe2 / WSe2 / C composite material prepared in Example 3 of the present invention was measured at a current density of 10A / g.
[0051] Figure 7 SEM images of the MoSe2 / WSe2 / C composite materials prepared in Examples 4 and 5 are shown; where A is Example 4 (LiCl); B is Example 5 (NaCl); scale bar 2 μm.
[0052] Figure 8 The graph shows the long-cycle performance of the MoSe2 / WSe2 / C composite material prepared in Example 3 as a potassium-ion battery anode at a current density of 5 A / g.
[0053] Figure 9 The image shows a SEM image of the MoSe2 / WSe2 / C composite material prepared in Comparative Example 1, with a scale bar of 1 μm. Detailed Implementation
[0054] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0055] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0056] Example 1: Preparation of MoSe2 / C composite material (comparative example) 0.5 mmol ammonium molybdate, 1 mmol selenite, and 1 g κ-carrageenan were uniformly dissolved in 100 mL deionized water at 80 °C. Then, 40 g potassium chloride was added under vigorous stirring, and stirring was continued for 1 h to form a homogeneous turbid solution.
[0057] The above turbid liquid was frozen in a -40 ℃ refrigerator for 36 h, and then dried in a vacuum freeze dryer (cold trap temperature -50 ℃, vacuum degree <10 Pa) for 48 h to obtain a fluffy solid precursor.
[0058] The precursor was placed in a tube furnace and heated to 700 °C at a heating rate of 2 °C / min under N2 atmosphere, and held for 1 h.
[0059] After natural cooling, the product was washed five times with deionized water to remove KCl and soluble impurities. It was then dried in a vacuum oven at 80 °C for 12 h to obtain a black powder product, denoted as MoSe2 / C.
[0060] The obtained MoSe2 / C sample was characterized by XRD, and the characterization results are as follows: Figure 1 As shown. Figure 1 As shown in the XRD pattern, the diffraction peaks of the MoSe2 / C composite material prepared in Example 1 are in good agreement with the hexagonal MoSe2 standard card (PDF No. 29–0914), and no other impurity peaks were observed, indicating that the pure phase MoSe2 / C composite material was successfully prepared.
[0061] Example 2: Preparation of WSe2 / C composite material (comparative example) The method in this embodiment is basically the same as that in Example 1, except that 0.5 mmol ammonium molybdate is replaced with 0.5 mmol ammonium tungstate, and no ammonium molybdate is added. The resulting sample is denoted as WSe2 / C. It is characterized by XRD, and the characterization results are as follows: Figure 1 As shown. Figure 1 As shown in the XRD pattern, the diffraction peaks of the WSe2 / C composite material prepared in Example 2 are in good agreement with the hexagonal WSe2 standard card (PDF No. 38–1388), and no other impurity peaks were observed, indicating that the pure phase WSe2 / C composite material was successfully prepared.
[0062] Example 3: Preparation of MoSe2 / WSe2 / C composite material Step 1: Preparation of precursor solution Weigh out ammonium molybdate (0.5 mmol), ammonium tungstate (0.5 mmol), selenite (1 mmol), and κ-carrageenan (1 g), and dissolve them in 100 mL of deionized water at 80℃, stirring until completely dissolved.
[0063] Add KCl (40 g) and continue stirring for 1 hour to form a uniform turbid liquid.
[0064] Step 2: Freeze-drying The above turbid liquid was transferred to a -40°C freezer and frozen for 36 hours, and then placed in a freeze dryer (cold trap temperature -50°C, vacuum degree <10 Pa) and dried for 48 hours to obtain a fluffy solid precursor.
[0065] Step 3: High-temperature calcination The precursor was placed in a tube furnace and heated to 700°C in a N2 atmosphere at a heating rate of 2°C / min, and held for 1 hour.
[0066] Step 4: Post-processing After natural cooling, the product was washed five times with deionized water to remove KCl and soluble impurities.
[0067] The product was dried under vacuum at 80℃ for 12 hours to obtain a black powder. The resulting sample was denoted as MoSe2 / WSe2 / C.
[0068] The obtained MoSe2 / WSe2 / C sample was characterized by XRD / SEM and TEM. Figure 1 As shown in the XRD pattern, the diffraction peaks of Example 3 correspond to both MoSe2 and WSe2 (card numbers: PDF No. 29–0914 and PDF No. 38–1388, respectively), and no other impurity peaks are observed, confirming the successful construction of the heterostructure. Figure 2 SEM images show that the MoSe2 / WSe2 / C composite material exhibits a macroscopic layered morphology, with MoSe2 / WSe2 nanosheets tightly anchored on an ultrathin carbon matrix. Figure 2 China A Figure 2 (B)
[0069] Figure 3 The TEM images further revealed that a tight and ordered heterogeneous interface was formed between the MoSe2 and WSe2 nanosheets, and a quasi-Mohr superlattice structure appeared; at the same time, an ultrathin carbon layer was uniformly coated on the surface of the heterojunction nanosheets, forming a typical "carbon encapsulation" structure.
[0070] Example 4: Preparation of MoSe2 / WSe2 / C composite material The operation steps in this embodiment are basically the same as those in embodiment 3, except that the salt template agent in step 1 of embodiment 3 is replaced with "40 g KCl" instead of "40 g LiCl". Figure 7 The SEM image of A shows that the MoSe2 / WSe2 / C composite material exhibits a macroscopic layered morphology, with MoSe2 / WSe2 nanosheets tightly anchored on the ultrathin carbon matrix.
[0071] Example 5: Preparation of MoSe2 / WSe2 / C composite material The operation steps in this embodiment are basically the same as those in embodiment 3, except that the salt template agent in step 1 of embodiment 3 is replaced with "40 g KCl" instead of "40 g NaCl". Figure 7 The SEM image of B shows that the MoSe2 / WSe2 / C composite material exhibits a macroscopic layered morphology, with MoSe2 / WSe2 nanosheets tightly anchored on the ultrathin carbon matrix.
[0072] Application Example 1: Assembly and Testing of Potassium-ion Batteries The MoSe2 / WSe2 / C nanocomposite material prepared in Example 3 was added to N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 8:1:1 with a conductive agent (acetylene black) and a binder (polyvinylidene fluoride PVDF) to form a homogeneous slurry. The slurry was coated onto copper foil, dried, and then die-cut to prepare a negative electrode sheet. A CR2032 type potassium-ion half-cell was assembled in a glove box under argon atmosphere, using a potassium metal sheet as the counter electrode and a 1M KFSI EC / DEC (volume ratio 1:1) solution as the electrolyte. The half-cell was tested using an electrochemical workstation and a Blue Battery testing system. The results are as follows: Figure 4 As shown.
[0073] from Figure 4 The rate performance curves show that the MoSe2 / WSe2 / C electrode performs well at rates of 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, and 10.0 A g. -1 At current densities of 405, 353, 316, 296, 266, 216 and 182 mAh g, respectively, were observed. -1 When the current density returns to 0.1 A g -1 The capacity was restored to 405 mAh g. -1 It exhibits excellent rate performance, significantly better than Examples 1 and 2.
[0074] from Figure 8 The long-cycle performance test results show that after 2000 cycles at a high current density of 5 A / g, the MoSe2 / WSe2 / C electrode can still maintain a reversible capacity of 190 mAh / g, with a capacity retention rate as high as 87.9%, and the coulombic efficiency is always close to 100%, demonstrating ultra-long cycle stability and excellent electrochemical reversibility.
[0075] Application Example 2: Assembly and Testing of Potassium Ion Hybrid Capacitors The MoSe2 / WSe2 / C nanocomposite material prepared in Example 3 was used to fabricate a negative electrode sheet according to the method in Application Example 1, and then pre-potassium-treated. Using the pre-potassium-treated MoSe2 / WSe2 / C as the negative electrode and activated carbon (AC) as the positive electrode, a potassium-ion mixed capacitor (PIHC) was assembled in a glove box under argon atmosphere with a negative electrode to positive electrode active material mass ratio of 1:1 and a 1M KFSI EC / DEC (volume ratio 1:1) solution as the electrolyte. The capacitor was tested using an electrochemical workstation, and the results are as follows: Figure 5 and Figure 6 As shown.
[0076] from Figure 5 The energy-power density curve (Ragone plot) of the potassium ion hybrid capacitor shows its excellent electrochemical performance. At 0.5 A g... -1 At current densities, the energy density reaches as high as 155 Wh kg. -1 The corresponding power density is 498 W kg. -1 Even in 20 Ag -1 Even at high current densities, it can still maintain 55 Wh / kg. -1 Its energy density has high commercial value.
[0077] like Figure 6 The long-cycle performance graph is shown in the figure at 10 A g. -1 After 10,000 cycles at current density, the capacity retention rate remains as high as 95.6%, demonstrating excellent cycle life and promising practical application prospects.
[0078] Comparative Example 1: Preparation of MoSe2 / WSe2 / C composite material without using a salt template (KCl dosage is 0) The operating steps of this comparative example are basically the same as those of Example 3, the only difference being that no salt template agent is added (KCl dosage is 0). Figure 9 The SEM images show that the nanosheets are severely stacked and fail to form a uniformly dispersed layered structure; the carbon layers are unevenly distributed, with some areas exposed.
[0079] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a carbon encapsulated heterojunction composite material, characterized by, Includes the following steps: (a) A precursor solution is formed by dissolving a molybdenum source, a tungsten source, a selenium source, a carbon source, and a salt template agent in a solvent; the salt template agent is potassium chloride; the carbon source is carrageenan; the molybdenum source is ammonium molybdate; the tungsten source is ammonium tungstate; and the selenium source is selenite; the molar ratio of the molybdenum source to the tungsten source is 1:0.5~2; the amount of the selenium source is 2~4 times the total molar amount of the molybdenum source and the tungsten source; and the mass of the salt template agent is 10-20 times the total mass of the molybdenum source, the tungsten source, the selenium source, and the carbon source. (b) Freeze-dry the precursor solution to obtain a solid precursor; the freeze-drying temperature is -50°C to -30°C and the time is 24-48 hours. (c) Under an inert atmosphere, the solid precursor is heated to 650-800°C for calcination to obtain the calcined product; (d) The calcined product is washed and dried to remove the salt template agent, resulting in a carbon-encapsulated molybdenum diselenide / tungsten diselenide heterojunction composite material. The composite material exhibits a macroscopic layered morphology, with MoSe2 / WSe2 nanosheets tightly anchored on an ultrathin carbon matrix to form a thin-layer carbon-coated structure. The MoSe2 / WSe2 nanosheets contain a continuous and ordered atomic arrangement, exhibiting a quasi-Mohr superlattice structure.
2. The preparation method according to claim 1, characterized in that, In step (c), the heating rate of the calcination is 1-5℃ / min, and the holding time is 0.5-3 hours.
3. A carbon-encapsulated heterojunction composite material, characterized in that, The composite material is prepared by the preparation method described in claim 1 or 2; the composite material exhibits a macroscopic layered morphology, with MoSe2 / WSe2 nanosheets tightly anchored on an ultrathin carbon matrix to form a thin-layer carbon-coated structure; the MoSe2 / WSe2 nanosheets have a continuous and ordered atomic arrangement inside, exhibiting a quasi-Mohr superlattice structure.
4. The application of the carbon-encapsulated heterojunction composite material of claim 3 in the preparation of potassium-ion battery anodes or potassium-ion hybrid capacitor anodes.
5. A potassium-ion battery or a potassium-ion hybrid capacitor, characterized in that, Its negative electrode comprises the carbon-encapsulated heterojunction composite material as described in claim 3.
Citation Information
Patent Citations
Transition metal chalcogenide nanosheet material and preparation method thereof, battery anode material, secondary battery and application thereof
CN109650348A
Carbon fiber-tungsten diselenide / molybdenum diselenide nanosheet heterojunction composite material and preparation method and application thereof
CN118825230A